Bryozoa—not a minor phylum - Gordon, Dennis; Costello, Mark (New Zealand Science Review, 2016)
​At the one-day symposium to mark the first author’s formal retirement, he gave a presentation titled ‘A life in bryo-zoology’, noting that he began publishing on Bryozoa in the late 1960s, with a taxonomic article in a student journal (Gordon 1967) followed by a paper in Nature (Gordon 1968). Of the 174 peer-reviewed papers published since then, 137 have focused on some aspect of bryozoology (e.g. ecology, conservation, growth, anatomy, ultrastructure, form and function, systematics, paleontology, phylogeny, marine fouling and invasive species, marine natural products). During the past 50 years of his research, perceptions of phylum Bryozoa in the scientific community have changed markedly from what was historically the case. The purpose of this short paper is to highlight what has changed.